Mums Go Online: Is the Internet Changing the Demand for Health Care? - Amaral-Garcia, Sofia; Nardotto, Mattia; Propper, Carol; Valletti, Tommaso (The Review of Economics and Statistics, 2022)
We study the effect of Internet diffusion on childbirth procedures performed in England between 2000 and 2011. We show that broadband Internet access increased cesarean sections (C-sections): mothers living in areas with better Internet access are 2.5% more likely to obtain a C-section. The effect is driven by first-time mothers who are 6% more likely to obtain a C-section. The increased C-section rate is not accompanied by changes in health care outcomes; thus health care costs increased with no corresponding medical benefits. We show evidence documenting the growing importance of the Internet as a source of health-related information.